Brief exercise induces an immediate and a delayed leucocytosis. - McCarthy, D A (1991)
Haematological profiles were measured: (1) before and for 5 h 30 min after 30 min sports (squash, swimming, jogging); and (2) before, during and for 2 h 30 min after 30 min cycle ergometry at workloads which required rates of oxygen consumption that were between 48% and 84% of maximal. In both instances exercise induced an immediate leucocytosis (owing to rises in both neutrophils and lymphocytes) which subsided rapidly at the finish of exercise and was followed by a delayed neutrophilia of greater magnitude which peaked at approximately 3 h after the start of exercise. Changes in plasma catecholamines and cortisol recorded during and after exercise (cycle ergometry only) support the hypothesis that the immediate leucocytosis during brief exercise is attributable to elevated catecholamine levels, whereas the delayed neutrophilia is due to raised cortisol levels.